Evolution and the missing link (in debunking arguments) - Leibowitz, Uri D.; Sinclair, Neil (Cambridge University Press, 2017)
What are the consequences, for human moral practice, of an evolutionary understanding of that practice? By ‘moral practice’ we mean the way in which human beings think, talk and debate in moral terms. We suggest that the proper upshot of such considerations is moderate support for anti-realism in ethics.